Parent-Teacher Interactions during COVID-19: Experiences of U.S. Teachers of Students with Severe Disabilities - Grace L. Francis; Alexandra R. Raines; Alexandra S. Reed; Marci Kinas Jerome (MDPI AG, 2022)
In 2020, COVID-19 disrupted all aspects of society across the globe including healthcare, employment, social interactions, and education. In many parts of the world, abrupt school closures caught teachers off guard, as they were forced to immediately shift their practices from in-person to online instruction with little-to-no preparation. Furthermore, during this time, many parents of school-aged children vacillated between multiple roles associated with their employment, household caregiving activities, and supporting their children at home. These challenges were especially challenging for teachers and parents of students with severe disabilities. The purpose of this study was to explore the experiences of U.S. teachers of students with severe disabilities regarding interacting with parents during the COVID-19 pandemic, including when schools initially closed in March 2020 and then reopened in September of 2020. This manuscript outlines six key themes highlighting parent-teacher interactions: (a) parents directing school decisions, (b) teacher inability to meet parent expectations, (c) parent-teacher communication, (d) parents as teachers, (e) parent exhaustion, and (f) teacher helplessness.